Erosive pustular dermatosis of the scalp: a pathogenetic мystery and therapeutic challenge - Georgi Tchernev; Simona Kordeva; Ilia Batashki; Atanas Batashki; Heily Kirilova; Konstantin Stavrov (Dermatology Reports, 2022)
Erosive pustular dermatosis of the scalp (EPDS) is a rare condition which affects predominantly the adult population, and occurs on a previously photo-damaged bald scalp. The physical examination is presented with a large erythematous, erosive and crusted patches with granulation on an atrophic skin. The problem in patients with erosive pustular dermatosis of the scalp arises from the nonspecific clinical and histopathological findings, which can be misleading. Biopsy followed by careful histopathological verification is mandatory, although the finding is nonspecific.The histopathology findings are characterized by superficial erosions with mild neutrophil infiltrate, mainly intravascular and focally with neutrophil exocytosis. Focal parakeratosis, smoothed rete ridges without pronounced interface changes. Pronounced lymphoplasmacytic infiltrate with focal distribution in the dermis, giant cell reaction with the formation of a “foreign body” granuloma. We report a 58-year old male patient with a 1 year old lesion, suspected for skin cancer, later diagnosed with EPDS, which was successfully treated with topical clobetasol proprionate after 3-5 weeks.